SARS-CoV-2 and MERS-CoV disrupt host protein synthesis via nsp1 with differential effects on the integrated stress response - Nicholas A. Parenti; Renee Cusic; David M. Renner; Nathaniel Jackson; Chengjin Ye; Li Hui Tan; Jessica J. Pfannenstiel; Anthony R. Fehr; Noam A. Cohen; Luis Martinez-Sobrido; James M. Burke; Susan R. Weiss (Proceedings of the National Academy of Sciences, 2026)
Coronaviruses pose a serious threat to public health, driving the need for antiviral therapeutics and vaccines. Therefore, it is paramount to understand how this family of viruses evades cellular antiviral responses and establishes productive infection. The conserved coronavirus nonstructural protein 1 (nsp1) has been shown to inhibit host protein synthesis and, in some coronaviruses, promote host messenger RNA (mRNA) degradation while viral mRNAs are protected. We showed previously that severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) induces activation of host integrated stress response (ISR) kinases protein kinase R (PKR) and PKR-like endoplasmic reticulum kinase (PERK), which promote phosphorylation of eukaryotic initiation factor 2 (eIF2α) and consequent inhibition of host protein synthesis. In contrast, eIF2α remains unphosphorylated during Middle East respiratory syndrome coronavirus (MERS-CoV) infection. To investigate the interactions of nsp1 and the ISR kinases, we utilized recombinant SARS-CoV-2 and MERS-CoV expressing nsp1 with mutations in each of two conserved domains. Upon infection with SARS-CoV-2 nsp1 mutants, translation was shut down in wildtype (WT) and PKR knockout (KO) cells but rescued in PERK KO cells, likely due to reduced p-eIF2α. In contrast, translation was rescued during infection with the analogous MERS-CoV nsp1 mutants even in WT cells. Moreover, SARS-CoV-2 WT suppressed expression of GADD34, a negative regulator of eIF2α phosphorylation, while SARS-CoV-2 nsp1 mutants induced GADD34. In contrast, MERS-CoV WT induced GADD34. Utilizing single-molecule fluorescence in situ hybridization, we found that SARS-CoV-2 and MERS-CoV nsp1 promote host mRNA degradation during WT, but not nsp1 mutant, infection. Thus, SARS-CoV-2 and MERS-CoV differ in interactions with the ISR and nsp1 control of host protein synthesis.